The Rise of the Justice Industry and the Decline of Legal Ethics - Robert B. McKay (Washington University Law Quarterly, 1990)
My friends, I am worried about the present health and the future well-being of a profession that has allowed many of us to do interesting, personally profitable, and possibly even useful things. Certainly, the law has been good to me. I come to criticize and complain, but not as an apostle of apocalypse. There is, I believe, hope of salvation, which will require all of us to join hands in what must ultimately lead to collective action in the name of-I do not shy from the word-justice. As you may now suspect, my message is cast in contradictory terms. I take my theme from the famous opening lines of Charles Dickens' cautionary parable about the French Revolution: "It was the best of times, it was the worst of times."' The same is true of the legal profession. Legal education has never been more apparently prosperous. But one wonders whether tuition can continue to rise to unchecked heights of student debt, and whether it is acceptable for students to view law school as a place of repose between the competition for admission to the school of choice and the competition, following soon after, for placement in the firm of choice at previously unimagined rates of compensation. The profession has similarly never offered more remuneration for lawyers- on the average. But for every million-dollar income, what about those at the other end of the scale? What about billable hours and quality of life? The organized bar has developed a conscience in recent decades-at least about the large issues. But what about mounting greed and increasing insensitivity to ethical concerns? What, in short, about law as a business, no longer a profession?
Keywords: Legal ethics; Practice of law